2011
DOI: 10.1161/hypertensionaha.111.177022
|View full text |Cite
|
Sign up to set email alerts
|

Parental History of Hypertension Is Associated With Narrower Retinal Arteriolar Caliber in Young Girls

Abstract: Abstract-We aimed to assess the associations between parental history of hypertension and indicators of cardiovascular risk (retinal vessel diameter, presence of obesity, and elevated blood pressure) in prepubertal children. There were 1739 (77.7% of those eligible) 6-year-old students (863 girls and 876 boys) who were examined from a random cluster sample of 34 Sydney schools. Parents completed questionnaires about their medical conditions, including whether they have/had hypertension. Retinal images were tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…52 A 2011 study reported that 6-year-old daughters but not sons of hypertensive parents were more likely to have narrower retinal arterioles than daughters of parents who did not have hypertension. 53 It is also possible that changes in some factors (e.g., a history of CVD) associated with wider CRVE may be balanced by factors associated with narrower CRVE (e.g., stopping smoking). The relationship of smaller CRVE with increasing age may partially be due to selective survival.…”
Section: Discussionmentioning
confidence: 99%
“…52 A 2011 study reported that 6-year-old daughters but not sons of hypertensive parents were more likely to have narrower retinal arterioles than daughters of parents who did not have hypertension. 53 It is also possible that changes in some factors (e.g., a history of CVD) associated with wider CRVE may be balanced by factors associated with narrower CRVE (e.g., stopping smoking). The relationship of smaller CRVE with increasing age may partially be due to selective survival.…”
Section: Discussionmentioning
confidence: 99%
“…Family history of HTN or CV disease may identify children and adolescents with essential HTN, but history of hereditary diseases associated with secondary forms of HTN should also be relevant (1,37). Parental history of HTN has been associated with masked HTN, early TOD, changes in central and peripheral hemodynamics, and can guide further evaluation (79,(93)(94)(95). A complete clinical history assessment may include information summaraised in Table 4.2.1.…”
Section: Family and Clinical Historymentioning
confidence: 99%
“…These covariates were selected based on their associations with placental function or the outcomes of interest based on previous studies or a change in the effect estimate of >10%. 12,[16][17][18] Table S2 shows the associations of each covariate with the outcomes of interest. Next, these models were additionally adjusted for gestational age at birth, birth weight, and child's current body mass index and blood pressure to explore whether the observed associations were explained by birth or childhood characteristics.…”
Section: Statistical Analysesmentioning
confidence: 99%